Android-Based Mobile Learning Media: Developing Short Functional Text Media for Eighth-Grade Students - Yulista, Ageng Wulan; Ifadah, Muhimatul; Wijayatiningsih, Testiana Deni; Darwis, Djamaluddin; Maulidina, Yunita Putri; Hairulla, Monera A. Salic (English Education: Jurnal Tadris Bahasa Inggris, 2024)
The purpose of this study was twofold: to develop an online learning application compatible with both Android and Windows platforms and to evaluate the effectiveness of an Android-based mobile learning tool in improving English proficiency and student perceptions. This research employed a research and development (R&D) methodology encompassing nine stages: needs assessment, data collection, product design, expert validation, testing, initial revision, trial implementation, second revision, and finalization. Data were collected through tests and questionnaires and analyzed using independent sample t-tests and descriptive statistics. Participants included second-year junior high school students in Central Java. The findings of this study are as follows: first, the validity of the developed product was confirmed through expert validation from media and material specialists, indicating its feasibility for educational use. Second, a statistically significant improvement in students’ test scores was observed, highlighting the effectiveness of the Android-based mobile learning tool. Finally, 75.5% of participants agreed that the application provided a positive learning experience by delivering practical and concise materials on greeting cards, enhancing engagement, and reducing learning monotony. This study demonstrates that Android-based mobile learning media can be a valuable tool for English language instruction.